Self-reported occupant behaviours and multi-domain comfort preferences in New Zealand tertiary office buildings - weerasinghe, A; Rasheed, E; Rotimi, J (Massey University, 2022)
Often, building occupants compromise the energy savings of the building when they modulate their comfort through occupant behaviours. Significant energy impacts are possible through these occupant actions. Therefore, it is necessary to reduce energy consumption and emissions while considering the effects of occupant behaviour based on the occupants' comfort preferences. This study identifies the interrelation between occupants' indoor environment comfort preferences on occupant energy behaviours in New Zealand office buildings. The research used a case study approach with interviewing 25 participants and surveying 52 occupants selected from five educational office buildings. The data were analysed using content analysis and descriptive analysis to draw the findings. Results show that more than 50% of occupants adjust windows, lighting, shades, blinds, computers, heating appliances, drink hot/cold beverages, and adjust clothing to cope with indoor environmental discomfort. Amongst, drinking hot and cold beverages (77%) and opening and closing windows (73%) are most prominent. Specifically, more than 60% of occupants were expected to let in the fresh air, increase air movement, feel cooler, and feel warmer through opening/closing windows, drinking hot/cold beverages, adjusting clothing, and personal heaters. Therefore, air quality and thermal comfort preferences are more prominent than visual and acoustic preferences. The findings from the current study would assist design buildings that maintain occupant comfort. Energy modelers could also use this information to improve occupant energy models for accurate energy consumption prediction.